The Idea of Informal-Based Social Education in Indonesian Islamic Boarding Schools - Anwar Hafidzi; Faqih El Wafa; Anida Yuspa; Mohd Hatta Md Hani (Journal of Contemporary Islamic Education, 2023)
The purpose of this study is to investigate the effect that open, distance, and technology-based informal or non-formal learning has on the growth of students who had previously attended an Islamic boarding school. This perspective originates from the fact that it is anticipated that the community-based learning approach will comprise between 75 and 90 percent of his life once he completes his education at an Islamic boarding school. Nevertheless, education is not simply mirrored accurately in the learning literature; rather, it must be desire-driven and contain future business skills. The library research technique is what was used for the research for this study, and it was chosen on the basis of our observations of the current education system in Indonesia. This is done to ensure that the education that children get in Islamic Boarding Schools is not solely focused on receiving a formal or certified education, but also places an emphasis on the students' excellent accomplishments. The findings of this study will ultimately establish the feasibility of improved outcomes, as well as the quality of such outcomes, and will generate favorable effects.